Survival outcomes for postoperative chemoradiation in intermediate‐risk oral tongue cancers. Issue 12 (27th September 2017) - Spiotto, Michael T.; Jefferson, Gina D.; Wenig, Barry; Markiewicz, Michael R.; Weichselbaum, Ralph R.; Koshy, Matthew
Abstract: Background: The survival outcomes for surgery + postoperative radiotherapy (S+RT) or surgery + postoperative chemoradiation (S+CRT) was compared in patients having oral tongue cancers with intermediate‐risk pathological features. Methods: Using the National Cancer Database (NCDB), overall survival (OS) for S+RT or S+CRT was estimated using the Kaplan‐Meier methods and Cox proportional hazard models in the entire population (n = 2803) and in a propensity‐matched cohort (n = 1136). Results: The 3‐year OS was 73.3% for S+CRT versus 66.7% for S+RT ( P = .02). The S+CRT improved the 3‐year OS for patients with 2 or more involved metastatic lymph nodes (≥2 MLNs; P = .01) but not for patients with <2 MLNs ( P = .73). Undergoing S+CRT improved the 3‐year OS for patients with pathologic T classification (pT) pT3‐pT4 disease ( P = .01) but not for patients with pT1‐pT2 disease ( P = .18). Conclusion: Undergoing S+CRT was associated with improved survival for patients with tongue cancers with ≥2 MLNs and/or pT3‐pT4 suggesting that specific intermediate‐risk pathological features benefit from treatment intensification.